72.1k views
4 votes
Match each function formula with the corresponding transformation of the parent function y = -4 x . .

1. y = -4x - 1 ANSWERS
Translated right by 1 unit
2. y = 1 - 4x Translated down 1 unit
3. y = -4-x Reflected across the x-axis
4. y = -4x + 1 Reflected across the y-axis
5. y = 4x Translated up by 1 unit
6. y = -1 - 4x Translated left by 1 unit

User Pasta
by
5.4k points

1 Answer

0 votes

Answer:

1. y = - 4(x - 1) ⇒ Translated right by 1 unit

2. y = 1 - 4x ⇒ Translated up by 1 unit

3. y = - 4(-x) ⇒ Reflected across the y-axis

4. y = - 4(x + 1) ⇒ Translated left by 1 unit

5. y = 4x ⇒ Reflected across the x-axis

6. y = -1 - 4x ⇒ Translated down by 1 unit

Explanation:

Lets explain how to solve the problem

- If the function f(x) reflected across the x-axis, then the new

function g(x) = - f(x)

- If the function f(x) reflected across the y-axis, then the new

function g(x) = f(-x)

- If the function f(x) translated horizontally to the right

by h units, then the new function g(x) = f(x - h)

- If the function f(x) translated horizontally to the left

by h units, then the new function g(x) = f(x + h)

- If the function f(x) translated vertically up

by k units, then the new function g(x) = f(x) + k

- If the function f(x) translated vertically down

by k units, then the new function g(x) = f(x) – k

* Lets solve the problem

∵ y = - 4x is the parent function

- The function after some transformation is:

1. y = - 4(x - 1)

∵ We subtract 1 from x

∴ The function translated right by 1 unit

y = - 4(x - 1) ⇒ Translated right by 1 unit

2. y = 1 - 4x

∵ We add 1 to y = - 4x

∴ The function translated up by 1 unit

y = 1 - 4x ⇒ Translated up by 1 unit

3. y = -4(-x)

∵ We multiply x by (-)

∴ The function reflected across the y-axis

y = - 4(-x) ⇒ Reflected across the y-axis

4. y = -4(x + 1)

∵ We add 1 to x

∴ The function translated left by 1 unit

y = - 4(x - 1) ⇒ Translated left by 1 unit

5. y = 4x

∵ We multiply y = - 4x by (-)

∴ The function reflected across the x-axis

y = 4x ⇒ Reflected across the x-axis

6. y = -1 - 4x

∵ We subtract 1 from y = - 4x

∴ The function translated down by 1 unit

y = -1 - 4x ⇒ Translated down by 1 unit

User Andrey Frolov
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.